The Mannoprotein Cig1 Supports Iron Acquisition From Heme and Virulence in the Pathogenic Fungus Cryptococcus neoformans - Cadieux, Brigitte (Oxford University Press, 2013)
Iron acquisition is critical for virulence of the human pathogenic fungus Cryptococcus neoformans. The cryptococcal transcript for the extracellular mannoprotein Cig1 is highly regulated by iron and abundant in iron-starved cells, suggesting a role in iron acquisition. Indeed, loss of Cig1 resulted in delayed growth on heme at physiological pH. Expression of CIG1 is regulated by the pH-responsive transcription factor Rim101, and loss of Rim101 also impaired growth on heme. A cig1Δ mutant was less susceptible than the wild-type strain to noniron metalloporphyrins, further indicating a role for Cig1 in heme uptake. Recombinant Cig1 exhibited the absorbance spectrum of a heme-binding protein upon heme titration, and Cig1 may therefore function as a hemophore at the cell surface. Cig1 contributed to virulence in a mouse model of cryptococcosis but only in a mutant that also lacked the high-affinity iron uptake system. Overall, Cig1-mediated heme uptake is a potential therapeutic target in C. neoformans.